APPLICATION OF THE PROJECT-BASED LEARNING MODEL IN ELEMENTARY SOCIAL STUDIES LEARNING PLANNING TO DEVELOP 21ST CENTURY SKILLS - Erlina Yuliastuti (CV. RADJA PUBLIKA, 2025)
This study aims to describe the application of the Project-Based Learning (PjBL) model in Social Science (IPS) learning planning in elementary schools and its contribution in developing 21st century skills. The research approach used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. The subjects of the study are classroom teachers and grade V students in one of the public elementary schools who have implemented a project-based curriculum. The results of the study show that PjBL-based social studies learning planning is carried out by compiling integrative and contextual learning objectives, and actively involving students in projects related to real problems in the surrounding environment. The implementation of PjBL encourages the development of students' critical thinking, collaboration, communication, and creativity skills. Although several obstacles were found such as differences in students' abilities and limited facilities, teachers were able to overcome them through adaptive strategies. In conclusion, the PjBL model is effective in increasing student learning engagement and is relevant to shaping the character and skills needed in the 21st century.